Permaculture’s lessons - Boyano, Daniel (Revista Española de Desarrollo y Cooperación, 2023)
In this approach to permaculture, it has been opted for, on one hand, to avoid the accumulation of statistical data, moreover difficult to locate because of the atomization, permacultural process isolation, and scant literature, and on the other hand, to avoid to avoid premature aging of the current text. The following text also analyze deeply the term of permaculture and its evolution in the recent years, but without forgetting that it is a set of techniques that, with other names has been, individually and collectively, performed for the whole humanity history in a local scale.